2013
DOI: 10.1007/10_2013_201
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free Biosystems in the Production of Electricity and Bioenergy

Abstract: : Increasing needs of green energy and concerns of climate change are motivating intensive R&D efforts toward the low-cost production of electricity and bioenergy, such as hydrogen, alcohols, and jet fuel, from renewable sugars. Cell-free biosystems for biomanufacturing (CFB2) have been suggested as an emerging platform to replace mainstream microbial fermentation for the cost-effective production of some biocommodities. As compared to whole-cell factories, cell-free biosystems comprised of synthetic enzymatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 147 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the efficiency of the system presented herein, could be further improved by replacing expensive nucleoside triphosphates (NTPs) with nucleoside monophosphate (NMPs) and exploit the endogenous enzymes to regenerate NTPs (Calhoun and Swartz, 2005;Jewett et al, 2008) The novel ATP-regeneration system presented in this work is suitable for semi-and continuous systems for in vitro protein synthesis (Spirin and Swartz, 2008), industrial applications (Swartz, 2006), high-throughput experiments (Caschera et al, 2011) and large-scale reaction using cell-free or enzyme technology (Butler, 1977). Our study also demonstrates that cell-free transcription-translation systems are valuable platforms for understanding and developing novel metabolic pathways (Zhang et al, 2007;Zhu et al, 2013).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the efficiency of the system presented herein, could be further improved by replacing expensive nucleoside triphosphates (NTPs) with nucleoside monophosphate (NMPs) and exploit the endogenous enzymes to regenerate NTPs (Calhoun and Swartz, 2005;Jewett et al, 2008) The novel ATP-regeneration system presented in this work is suitable for semi-and continuous systems for in vitro protein synthesis (Spirin and Swartz, 2008), industrial applications (Swartz, 2006), high-throughput experiments (Caschera et al, 2011) and large-scale reaction using cell-free or enzyme technology (Butler, 1977). Our study also demonstrates that cell-free transcription-translation systems are valuable platforms for understanding and developing novel metabolic pathways (Zhang et al, 2007;Zhu et al, 2013).…”
Section: Resultsmentioning
confidence: 81%
“…We demonstrate that hexametaphosphate (HMP), a polyphosphate molecule (NaPO 3 ) 17 , is efficiently used to fuel protein synthesis when coupled to a carbon source such as maltose or maltodextrin. In addition to reduce the cost of the ATP-regenerating system, we develop new knowledge of in vitro metabolic pathways and provide an alternative system to a rapidly growing research area (Carlson et al, 2012;Zhu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial analogs can substitute for expensive cofactors [ 118 ] and can be designed to be more stable than their natural counterparts while still being recognized by enzymes. The CoA cycle is crucial for PHA synthesis, but its dependence on chemicals for cofactor repair in vitro hinders CoA from being stable for extended periods [ 119 ]. More comprehensive reviews of cofactor and ATP regeneration systems have been reported [ 110 , 120 , 121 ].…”
Section: Advantages and Prospects For In Vitro Pha Synthesismentioning
confidence: 99%
“…Although each of these challenges can be addressed from multiple aspects, some potential solutions are too complex to implement and may also be detrimental factors in terms of other aspects of cell performance. Due to the complexity of these challenges, a systematic analysis should be made to identify the key reasons behind each challenge and to then carefully evaluate multiple possible solutions …”
Section: Introductionmentioning
confidence: 99%